Liberalization of agriculture equipment: Lessons and challenges from the cashew value in Mozambique (Research, Society and Development, 2023)
The adoption of subsidies in agriculture is a subject of international debate. However, Mozambique, in the late 90’s opted for the subsidies policy in the cashew production chain aiming at production and industry recovery. In the present study, the objective was to understand how the subsidies policy impacted on cashew production, what are the lessons and challenges arose from removal of subsidies and subsequent liberalization of pesticide application equipment. By sampling, 355 semi-structured interviews were conducted to the direct beneficiaries of subsidies for chemical spraying of cashew trees. The content of the questionnaire included among others the demographics, type and source of spraying equipment, year of purchase, number and efficiency of the service provided.  From IAM-IP database, number of beneficiaries and cashew nuts commercialized production were sourced. The data were processed using descriptive statistics and graphically plotting the distribution of frequencies correlations in Excel. The results indicate that the subsidies policy covered up to 14% of cashew producers households and boosted the commercialized production from 50 thousand tons to trice. It generated 9.208 permanent jobs opportunities for man (95%) between 46 and 60 years (49%) of heterogeneous literacy. Removal of subsidies and liberalization of spraying equipment expanded the purchase of more equipment, but the quality declined. Therefore, in a liberalized market system, associated subsidies, must be repurposed towards research, regulations and monitoring of efficiency and quality of both equipment and services provided. This lesson can be extrapolated for the current subsidies on pesticides.